CRSCA booklet 2007 - University of Wisconsin-River Falls. Chalmer Davee Library (University of Wisconsin-River Falls. Chalmer Davee Library, 2008)
Booklet listing the articles, books, academic posters, fine and performance art, playbills and other items produced by the faculty and staff at the University of Wisconsin-River Falls during the 2007 calendar year.
23 p.
Keywords: University of Wisconsin-River Falls--Faculty--Research; Universities and colleges--Research--Wisconsin--River Falls; Chalmer Davee Library; University of Wisconsin-River Falls--Employees--Research; University of Wisconsin-River Falls--Faculty; University of Wisconsin-River Falls--Employees; University of Wisconsin-River Falls--Research; Universities and colleges--Wisconsin--River Falls--Employees; University of Wisconsin-River Falls. Chalmer Davee Library; CRSCA booklet; University of Wisconsin-River Falls; CRSCA; Celebrating research, scholarlship and creative achievement; Universities and colleges--Wisconsin--River Falls--Faculty